EFEKTIVITAS YOUTUBE SEBAGAI MEDIA PROMOSI PROGRAM STUDI ILMU KOMUNIKASI FISIP UNPAS - Muhammad Fazri Candra (Linimasa : Jurnal Ilmu Komunikasi, 2022)
This study aims to find out how effective YouTube is as a promotional media in the Pasundan University and the general public in improving the Pasundan University brand image. This study uses qualitative research methods in descriptive form. The problem in this study is how effective the YouTube PR media can be a campus promotion tool and a means to improve the Pasundan University brand image. The results of this study indicate that the youtube promotional media can easily attract public interest to seek information on the public relations youtube channel, thereby indirectly making many people who know about Pasundan University and the brand image of Pasundan University also increase. There are several obstacles experienced by the Public Relations of the University of Pasundan in building the YouTube channel of Public Relations from the beginning until now, starting from the internal campus which still does not know much about the Public Relations YouTube channel of the University of Pasundan to the limited ideas for creating content on the YouTube Public Relations of the University of Pasundan.